(untitled) (Archives of Criminology, 2006)
The opinions presenting sexual harassment as a form of sex-based discrimination appeared long before such a regulation was introduced. Today, both in legal acts and in the doctrine, sexual harassment is considered to be a sex-based discrimination. The same opinion is voiced by the legal practice of many countries. The paper aims at presenting the basic aspects of this problem and at reviewing the legal practice of these countries.